2018
DOI: 10.1016/j.ejmech.2018.03.059
|View full text |Cite
|
Sign up to set email alerts
|

Targeting the entrance channel of NNIBP: Discovery of diarylnicotinamide 1,4-disubstituted 1,2,3-triazoles as novel HIV-1 NNRTIs with high potency against wild-type and E138K mutant virus

Abstract: Inspired by our previous efforts on the modifications of diarylpyrimidines as HIV-1 non-nucleoside reverse transcriptase inhibitors (NNRTI) and reported crystallography study, novel diarylnicotinamide derivatives were designed with a "triazole tail" occupying the entrance channel in the NNRTI binding pocket of the reverse transcriptase to afford additional interactions. The newly designed compounds were then synthesized and evaluated for their anti-HIV activities in MT-4 cells. All the compounds showed excelle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
35
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(35 citation statements)
references
References 40 publications
0
35
0
Order By: Relevance
“…130 Moreover, 99 interacted strongly with recombinant HIV-1 CA and exhibited antiviral potential in the early and late stages of HIV-1 replication. New 1,4-disubstituted 1,2,3-triazole-bearing diarylnicotinamides were examined for anti-HIV potentials against wild-type (WT, IIIB and ROD) and multiple mutant strains by Tian et al 131 Three of the most potent lead derivatives identified were 100 (EC 50(IIIB) = 0.020 µM, EC 50(E138K) = 0.015 µM, CC 50 = 40.15 µM), 101 (EC 50(IIIB) = 0.020 µM, EC 50(E138K) = 0.014 µM, CC 50 = 58.09 µM), and 102 (EC 50(IIIB) = 0.020 µM, EC 50(E138K) = 0.027 µM, CC 50 = 180.90 µM; Fig. 12), which showed equal promising potency against the E138K mutant strain.…”
Section: Antiviral Activitymentioning
confidence: 99%
“…130 Moreover, 99 interacted strongly with recombinant HIV-1 CA and exhibited antiviral potential in the early and late stages of HIV-1 replication. New 1,4-disubstituted 1,2,3-triazole-bearing diarylnicotinamides were examined for anti-HIV potentials against wild-type (WT, IIIB and ROD) and multiple mutant strains by Tian et al 131 Three of the most potent lead derivatives identified were 100 (EC 50(IIIB) = 0.020 µM, EC 50(E138K) = 0.015 µM, CC 50 = 40.15 µM), 101 (EC 50(IIIB) = 0.020 µM, EC 50(E138K) = 0.014 µM, CC 50 = 58.09 µM), and 102 (EC 50(IIIB) = 0.020 µM, EC 50(E138K) = 0.027 µM, CC 50 = 180.90 µM; Fig. 12), which showed equal promising potency against the E138K mutant strain.…”
Section: Antiviral Activitymentioning
confidence: 99%
“…The results indicate that the presence of nitro and cyano group at the 3 rd position on benzyl ring 63 increases the activity of the compound against HIV-1, as shown in the molecule. 103 Phenylalanine derivatives that were also synthesized via click chemistry exhibit excellent anti-HIV activity. Compound 64 has very high activity against HIV-1 NL4-3 strain with much lesser toxicity because of the presence of b-substituted naphthalene, which is directly bound to triazole.…”
Section: Introductionmentioning
confidence: 99%
“…great attention due to their extensive biological properties such as antioxidant, [5] antifungal, [6,7] antitubercular, [8] antibacterial, [9] anticancer, [10] anti-HIV, [11] antimicrobial, [12] and antimalarial activity. [13] The 1,4-disubstituted-1,2,3-triazoles were synthesized via coppercatalyzed azide-alkyne cycloaddition reaction, well known as a click chemistry reaction.…”
Section: Diversely Functionalized 123-triazole Derivatives Have Attmentioning
confidence: 99%